2010
DOI: 10.1093/europace/euq191
|View full text |Cite
|
Sign up to set email alerts
|

Acute severe mitral regurgitation as an early complication of pacemaker implantation

Abstract: A 70-year-old man developed drug refractory acute pulmonary oedema secondary to acute severe mitral regurgitation (MR) immediately after implantation of a dual-chamber pacemaker for complete heart block. Clinical improvement occurred after allowing the patient to resume his native rhythm. A new lead was positioned within the right ventricular outflow tract (RVOT). The echocardiogram during pacing at RVOT showed minimal MR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 2 publications
0
7
0
1
Order By: Relevance
“…Post-MitraClip hemodynamics confirmed dramatic improvement in left atrial pressures throughout both paced and native rhythms ( Figure 5, Table 1). Transthoracic echocardiography on postoperative day 1 showed a mild decrease in left ventricular size and modest drop in left ventricular ejection fraction from 60-65% to 45-50% but with sustained mild residual MR. clinical scenarios ranging from acute severe MR immediately following pacemaker implantation to slow progression of MR in the setting of chronic right ventricular apical pacing [4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…Post-MitraClip hemodynamics confirmed dramatic improvement in left atrial pressures throughout both paced and native rhythms ( Figure 5, Table 1). Transthoracic echocardiography on postoperative day 1 showed a mild decrease in left ventricular size and modest drop in left ventricular ejection fraction from 60-65% to 45-50% but with sustained mild residual MR. clinical scenarios ranging from acute severe MR immediately following pacemaker implantation to slow progression of MR in the setting of chronic right ventricular apical pacing [4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…The improvements in valvular regurgitation have come about through altering the site of right ventricular lead pacing to the interventricular septum [6], or placement in the right ventricular outflow tract [2]. Changing mode of pacing from VVI to atrial pacing with intrinsic ventricular rhythm has also been reported to improve MR [7].…”
Section: Discussionmentioning
confidence: 99%
“…Mitral regurgitation (MR) can worsen as a result of acute or chronic right ventricular apical pacing [1,2]. The mechanism is thought to be a consequence of intraventricular dyssynchrony and altered papillary muscle mechanics [3].…”
Section: Introductionmentioning
confidence: 99%
“…In 2010 Rita Miranda et al [14] continued problem of left atrium dysfunction. The authors first described acute mitral regurgitation complicated by pulmonary edema caused by RVA stimulation in short time observation.…”
Section: Left Atrium and Mitral Valve Dysfunction -Atrial Fibrillationmentioning
confidence: 99%